Predictive Design of Shear-Thickening Electrolytes for Safety Considerations. Issue 12 (1st January 2017) - Shen, Brian H.; Veith, Gabriel M.; Armstrong, Beth L.; Tenhaeff, Wyatt E.; Sacci, Robert L.
Abstract : Non-Newtonian, shear-thickening lithium-ion battery electrolytes show promise for improved safety in high impact events by exhibiting a reversible transition to a solid-like phase under high shear. This aids in the prevention of shorting and subsequent combustion of volatile electrolyte under such conditions. In this work, we investigate the electrodynamics of shear-thickening electrolytes using conductivity under shear measurements, as well as finite-element modeling. We observe an order of magnitude drop in ionic conductivity under shear-thickening conditions. We suggest a working model to explain substantial drops in conductivity observed in shear-thickening electrolytes under shear. The results here can be generally applied to any electrolyte that exhibits non-Newtonian hydrodynamic properties.